Opportunities and challenges for biofortification of cassava to address iron and zinc deficiency in Nigeria - Okwuonu, I.C.; Narayanan, N.N.; Egesi, Chiedozie N.; Taylor, N.J. (Elsevier, 2021)
Nigeria is the world's largest producer of cassava (Manihot esculenta), and its production is important to the country's economy. Cassava's edible storage roots act as a critical staple food for over 180 million Nigerians. Micronutrient deficiency presents a major public health issue in Nigeria and correlates with cassava consumption level across six-agro-ecological zones within the country. Though high in caloric value, cassava roots are deficient in minerals, placing populations that rely on this crop at risk of hidden hunger. Micronutrient deficiencies, especially iron and zinc, affect an estimated 6 million children in Nigeria under five years of age. Supplementation, fortification and food-based diversification are being employed to tackle micronutrient deficiencies. However, in order to achieve wider impact and sustainability, biofortification of staple foods such as cassava is also being explored. Conventional breeding of cassava is unlikely to achieve elevated storage root mineral content at nutritionally significant levels due to lack of genetic diversity for these traits within the existing germplasm. Biofortification by genetic modification provides a potential solution to this challenge. Proof of concept has demonstrated that transgenic biofortification is a reality and can produce foodstuffs with increased mineral content that could beneficially impact the health of consumers in Nigeria and elsewhere. This review is targeted towards understanding the dynamics of micronutrient deficiency across Nigeria and addresses opportunities and challenges for deploying iron and zinc biofortified cassava.